Effects Of Decompression Surgery On Pelvic Movements In Patients With Degenerative Lumbar Stenosis - Polat, Yusuf; Polat, Elif Aygün; Karatay, Gokhan Mehmet; Esmer, Murat; PHD, Esedullah Akaras; Kafa, Nihan; Best, Norman; Güzel, Nevin Atalay (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2023)
Objective Pelvic movements when walking should be objectively evaluated in the context of clinical data in order to understand the function of compensatory mechanisms in the onset and management of symptomatic degenerative lumbar stenosis (DLS). The purpose of this study was to compare patients treated with decompression surgery (DS) and patients with symptomatic DLS in terms of pelvic movements while walking.Materials and Methods A total of 107 participants were included in this study. 34 patients who underwent DS performed by the same surgeon were selected as the DS group, while 39 patients with DLS who required surgery were selected as the DLS group. The control group consisted of 34 age-matched healthy individuals who had no disease and no gait disorder. The BTS G-WALK sensor system (G-Walk) was used to measure pelvic movements (tilt, rotation, obliquity) and gait parameters (speed, cadence, stride length).Results DS and control groups had decreased maximum (p=0.008 and p=0.006, respectively) and minimum anterior tilt of the pelvis (p=0.015 and p=0.001, respectively) compared to the DLS group. There was no significant difference between the groups for rotation, oblique and tilt range of motion of the pelvis (p>0.05). Compared to the control group, speed during gait were significantly lower in both the DLS (p=0.012) and DS groups (p=0.016).Conclusions In this study, decompression surgery was found to affect pelvic movements. Patients with DLS walked differently from those who had no symptoms, and this difference usually disappeared following surgical decompression. Pelvic movements may serve as a helpful screening measure to identify early compensatory mechanisms. Key words: lumbar stenosis, pelvic movement, decompression surgery, spine-pelvis lower extremity, sagittal alignment
Keywords: lumbar stenosis; pelvic movement; decompression surgery; lower extremity; sagittal alignment